AUSTRALIAN DOMESTIC TOURISM DEMAND ANALYSIS USING PANEL DATA STATIC REGRESSION - Yap, Ghialy (Economic Journal of Emerging Markets, 2011)
The main aim of this research is to achieve sustainability of domestic tourism businesses in Australia. This study reveals several distinct findings. First, the income elasticity for domestic visitors of friends and relatives and interstate trips is negative, implying that Australian households will not choose to travel domestically when there is an increase in household income. Second, an increase in the current prices of domestic travel can cause the demand for domestic trips to fall in the next one or two quarters ahead. Third, the coefficients for lagged dependent variables are negative, indicating perhaps, that trips are made on a periodic basis. Keywords: Domestic visitors, domestic tourism, income elasticity, domestic travel JEL classification numbers: L83